1997
DOI: 10.1042/bj3230343
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of mitochondrial respiration and glycolysis in human leukaemic leucocytes by methylglyoxal

Abstract: The effect of methylglyoxal on the oxygen consumption of mitochondria of both normal and leukaemic leucocytes was tested by using different respiratory substrates and complex specific artificial electron donors and inhibitors. The results indicate that methylglyoxal strongly inhibits mitochondrial respiration in leukaemic leucocytes, whereas, at a much higher concentration, methylglyoxal fails to inhibit mitochondrial respiration in normal leucocytes. Methylglyoxal strongly inhibits ADP-stimulated α-oxoglutara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 16 publications
3
54
0
2
Order By: Relevance
“…The concentrations of GO/MGO used here are similar to those generally used to evaluate the biological effects of these dicarbonyls (10,11,26,34) and are consistent with those (high micromolar range) found in living systems (35). Moreover, these concentrations are close to those used in vitro to generate AGE content in a physiological range (8,36).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The concentrations of GO/MGO used here are similar to those generally used to evaluate the biological effects of these dicarbonyls (10,11,26,34) and are consistent with those (high micromolar range) found in living systems (35). Moreover, these concentrations are close to those used in vitro to generate AGE content in a physiological range (8,36).…”
Section: Discussionsupporting
confidence: 53%
“…Modification of proteins through derivatization by GO and MGO may induce interaction with specific receptors, such as the RAGE and AGE-R family (9), or directly alter protein functions. For instance, MGO inhibits mitochondrial respiration, membrane ATPases and glyceraldehyde-3-phosphate dehydrogenases (10), and DNA and protein synthesis, thereby inducing growth arrest and cell death (11).…”
mentioning
confidence: 99%
“…Despite extensive studies on the role of glycolysis in the generation of MG as a glycating factor, data are scarce on such a modification of just glycolytic enzymes. It was shown that MG inhibits glycolysis in metastatic cells of Ehrlich tumor and leukemic leukocytes by the formation of glycated GAPDH [28,29]. Moreover, in vitro glycation with MG of that enzyme from rabbit muscle and also rabbit muscle lactate dehydrogenase (LDH) induces significant reductions in their catalytic activity in a dose-and time-dependent manner [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…6 The beauty of MG, a normal metabolite, lies in the fact that it kills exclusively cancer cells by inhibition of glycolysis and mitochondrial respiration, leaving no adverse effect on normal cells. 7,8 A detailed pharmacokinetic and toxicological study of MG confirmed that it is apparently devoid of any toxic effect. 9 MG can also activate macrophages 10 via superoxide and nitrite production through the MAPK/NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…This also supports our previous observation that MG can kill cancer cells by depleting energy production through inhibition of both glycolysis 8,34 and mitochondrial respiration 35,36 of malignant cells without affecting normal cells. 7,35,36 The apoptotic potential of Nano-MG has also been established in this study. HBL-100 cells were shown to be nearly twice more prone to apoptosis when treated with Nano-MG where the amount of MG was 40 times lower than MG in bare form.…”
mentioning
confidence: 99%